DASH-Based Multi-View Video Streaming System - Yun, Dooyeol; Chung, Kwangsue (IEEE transactions on circuits and systems for video technology, 2018)
With the rapid development of electronic and computing technology, multi-view video transmission has attracted significant attention from the research and industrial communities. A multi-view video service provides a user with various viewpoints according to the user's input. Alongside the recent trend of shifting video streaming service platforms to HTTP adaptive streaming, dynamic adaptive streaming over HTTP (DASH)-based multi-view video services has been widely studied. However, DASH-based multi-view video streaming suffers from high view-switching delay. The delay between a request for view switching and the rendering of the target view adversely affects the quality of experience. This paper provides an analysis of the view-switching delay of DASH-based multi-view video streaming. Based on the analysis, a novel DASH-based multi-view video streaming system is proposed. It can minimize the view-switching delay by employing a buffer control, parallel streaming, and server push schemes. The results obtained from the implementation of this solution show that the proposed system significantly reduces the view-switching delay while guaranteeing the quality of multi-view video.